COMPARISON OF OPERATIVE TIME AND LENGTH OF HOSPITAL STAY IN LAPAROSCOPIC CHOLECYSTECTOMY IN ACUTE VERSES CHRONIC CHOLECYSTITIS - Damani, Shireen A.A Ramzanali; Haider, Sadiqa; Bilal, Hazrat; Perveen, Sughra (Journal of Ayub Medical College Abbottabad, 2015)
Background: The laparoscopic surgery has opened a new era in the field of surgery. Currently, it is accepted as the gold standard in the treatment of symptomatic cholelithiasis. However, laparoscopic cholecystectomy (LC) performed for acute cholecystitis is technically difficult because of severe inflammatory adhesions and distortion of the biliary anatomy. The objective of this study was to compare the frequency, mean operative time and length of hospital stay in patients of acute and chronic cholecystitis undergoing laparoscopic cholecystectomy. Methods: This prospective comparative study was carried out in the department of General Surgery Jinnah Postgraduate Medical Centre (JPMC) Karachi, from March to September 2013. During this period 233 patients underwent laparoscopic cholecystectomy (54 cases of acute and 179 cases of chronic cholecystitis respectively). The patients who were pregnant, diagnosed with gall bladder mass on ultrasound, carcinoma gall bladder, acute pancreatitis, and those with co-morbid like diabetes mellitus/cardiovascular disorders were excluded. Result: A total of 233 patients were admitted for laparoscopic cholecystectomy. Fifty four (54) patients in Group A (acute cholecystitis) and 179 patients in Group B (chronic cholecystitis) with female: male 2.8:1 and 4:1 in Group A and B respectively. Operative time was longer for group A. Six cases of conversion to open procedure one (1) in Group A and 5 in Group B respectively. Conclusion: Laparoscopic cholecystectomy is safe and efficient for both acute and chronic cholecystitis. Keywords: Laparoscopic cholecystectomy, acute cholecystitis, chronic cholecystitis